Analisa Penggunaan Over Current Relay (OCR) Sebagai Alat Proteksi Pada Transformator Daya Gardu Induk Sekarputih PT.PLN (PERSERO) - Irfansyah, Mohammad Afif; Wati, Trisna (Prosiding Seminar Nasional Teknik Elektro, Sistem Informasi, dan Teknik Informatika (SNESTIK), 2024)
in the data at the Sekar Putih substation on a single side 70 kV transformer the short circuit disturbance is 14,505 kA for three phases and 0.647 kA for one phase to ground, while on the 150 kV side the three phase short circuit disturbance is 21,501 kA and 18,157 kA for one phase to ground . With this research, the aim of minimizing short circuit disturbances is that a relay is needed, namely the overcurrent relay (OCR), which is tasked with indicating the presence of short circuit currents occurring in the system. By increasing the OCR setting value using the PSO method, the TMS results and trip time (t) are very optimal. The results of this research show that the OCR setting on the OCR time setting (TMS) on a 150 kV single-sided transformer using the PSO method is 0.1124 seconds with a trip time (t) of 0.8191 seconds for a short circuit fault of 18,730 A, while using the manual calculation method TMS is 0.4 seconds with a trip time (t) of 1.237 seconds with a short circuit disturbance of 21.501 kA. Therefore, it can be concluded that by using the PSO method the TMS results and trip time (t) are faster and more efficient than using the conventional method.